Gluten-free cheese bread from frozen dough: effect of modified cassava starch - MESA,Erika (2019)
Abstract The freezing process in dough is widely used to improve fresh product availability for the consumer. The aim of the study was to assess the effect of different modified cassava starches on the quality and textural properties of gluten-free (GF) cheese bread made from frozen GF cheese dough. Three sour cassava starches (extra, express and yucauca) and two chemically modified starches (Expandex® (MCS) and Gel®Baking (OCS)) were used. Samples with sour cassava starches showed higher hardness and number of crumb pores than those with chemically modified starches. Furthermore, a better overall appearance was observed for samples with OCS. Hence, triangle test was carried out between samples with OCS and samples made from fresh dough (control). The consumer panelists identified differences between samples because the GF cheese breads with OCS showed higher compaction and hardness, and they were less salty in taste than the control samples.